Drivers of Customer Retention: An Introspection Into Indian Retail Customers - Jogi Mathew
There is a wide variety of choices for the modern retail customer including multiple retail formats. The success of the retail establishments has a great reliance of customer retention, which is an essential attribute to achieve profitability. This study takes in to consideration to extract the factors responsible for customer retention which in turn assists in increasing the customer base. The prime objective of the study is to ascertain the influence of customer satisfaction, switching costs and customer loyalty on customer retention. Whereas, the second one is to explore the effect of demographic factors on customer retention. The sample size of this study was 600 respondents who were chosen for the full-fledged study. The statistical techniques used for final analysis were structural equation modelling and regression. The findings subsequent to the statistical analysis and interpretation concluded that customer loyalty, customer satisfaction and switching cost have the strongest effect on customer retention in retails. Customer satisfaction alone is not every time an indicator of customer loyalty. A loyal customer will spread positive word of mouth to other prospective customers about the retail. Occupation of respondent has a major influence on customer retention dimensions.